1987
DOI: 10.1037/0735-7028.18.4.407
|View full text |Cite
|
Sign up to set email alerts
|

APIC guidelines: Are they really that helpful?

Abstract: The matching process for professional internships in psychology has been reviewed by many authors who label the process as being difficult and pressure filled. Currently, the Association of Psychology Internship Centers (APIC) stipulates guidelines to reduce this pressure on prospective interns and APIC members during the selection process. We anonymously surveyed 45 graduate students who recently completed the internship selection process. They reported both major and minor APIC guideline violations. Of those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Recommendations for addressing internship selection issues are presented.The predoctoral internship selection process has often been viewed as stressful by many individuals involved in this experience. In particular, over the years internship applicants have consistently reported that they encounter a great deal of stress in their efforts to find a training site (Allen & Dressel, 1992;Carifio, Buckner, & Grace, 1987;Norcross & Wogan, 1987). The Association of Psychology Postdoctoral and Internship Centers (APPIC) established guidelines on internship offers and acceptances to more clearly delineate the protocol associated with finding an internship site and to reduce the stress on applicants and APPIC members (APPIC, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations for addressing internship selection issues are presented.The predoctoral internship selection process has often been viewed as stressful by many individuals involved in this experience. In particular, over the years internship applicants have consistently reported that they encounter a great deal of stress in their efforts to find a training site (Allen & Dressel, 1992;Carifio, Buckner, & Grace, 1987;Norcross & Wogan, 1987). The Association of Psychology Postdoctoral and Internship Centers (APPIC) established guidelines on internship offers and acceptances to more clearly delineate the protocol associated with finding an internship site and to reduce the stress on applicants and APPIC members (APPIC, 1994).…”
mentioning
confidence: 99%
“…Despite numerous attempts over the years by APPIC to clarify the selection process, some (e.g., Johnson, 1986) have asserted that the process is fraught with ethical problems and is in need of significant revision. Carifio et al (1987) assessed the helpfulness of APPIC guidelines in mitigating the stress that many graduate students experience during the selection process. They found that "both major and minor violations of [APPIC] guidelines were frequent MADONNA G. CONSTANTINE received her PhD in counseling psychology from the University of Memphis.…”
mentioning
confidence: 99%
“…Laughlin and Worlay (1991) defended APPIC resolution of guideline violations but were countered by Carifio and Grace (1992), who stated that Laughlin and Worlay ignored documented complaints and gave a false impression of the adequacy of APPIC's ability to deal effectively with guideline violations. Two studies (Carifio, Buckner, & Grace, 1987; Constantine & Keilin, 1996) surveyed applicants and found frequent guideline violations. Plante (1987) argued that guideline problems could be improved by establishing a national application deadline date, guidelines regarding the time frame within which interviews are conducted, and stronger caveats against internship sites requiring feedback from applicants in advance of uniform notification day.…”
Section: The Intern Selection Processmentioning
confidence: 99%
“…In fact, over the years, it has been observed that some participants have engaged in an increasingly varied set of behaviors in an attempt to gain an advantage over other participants (Keilin, 1998). These behaviors, many of which violated either the spirit or the letter of the APPIC guidelines, resulted in significant levels of stress and anxiety for many participants (Allen & Dressel, 1992; Carafio, Buckner, & Grace, 1987).…”
mentioning
confidence: 99%